(untitled) (Latakia University Journal -Medical Sciences Series, 2018)
This study was aimed to evaluate the role of the internal layer of periosteum and the bone in osteogenesis in periosteal distraction. The sample consisted of 10 rabbits from local spices. The periosteal was distracted by using custom-made device which rigidly fixed to the lateral surface of the mandible of on side whether the other side was served as control. 5 rabbits were sacrificed at 4 weeks and 4 at 8 weeks of operation At 8 weeks the histological study showed cellular activity, a variable amount of bone tissue in form of lamellar bone with increasing in number of osteocyte and lining by osteoblast. In the space that faced the internal layer of periosteum. Almost, the same picture was seen in the space formed between the device and the bone. The new bone formation was limited to the small, separate and non-organized island separated with connective tissue. The complete isolation between the periosteum and the bone lead to a low dense new bone formation. تقييم دور الطبقة الداخلية للسمحاق والعظم في التشكل العظمي في سياق عملية تبعيد السمحاق هدف هذا البحث إلى تقييم دور كلا ً من الطبقة الداخلية للسمحاق والعظم في التشكل العظمي في سياق عملية تبعيد السمحاق. شملت عينة البحث عشرة أرانب من الزمر المحلية. تم تبعيد السمحاق عن طريق تطبيق جهاز من التيتانيوم مصنع خصيصا ً لهذه الدراسة بحيث تم تثبيت الجهاز على الوجه الوحشي للفك السفلي على أحد الجانبين بينما اعتبر الجانب الآخر كشاهد. تم التضحية بخمسة أرانب بعد أربعة أسابيع وخمسة أرانب بعد 8 أسابيع من الإجراء الجراحي. أظهرت المقاطع النسيجية للنسيج المأخوذ من الفراغ المتشكل بين الطبقة الداخلية للسمحاق وبين الجهاز بعد ثمانية أسابيع من العمل الجراحي نشاط خلوي واضح مع وجود كميات مختلفة من نسج عظمية على شكل عظم صفائحي مع زيادة في عدد الخلايا العظمية بداخله كما يحاط هذا العظم بعدد وافر من الخلايا البانية للعظم ونفس الصورة النسيجية تقريبا ً لوحظت في المقاطع النسيجية المأخوذة من الفراغ المتشكل بين الجهاز وبين العظم حيث اقتصر التشكل العظمي على جزر عظمية صغيرة ومنفصلة وغير منتظمة مفصولة بنسيج ضام. إن عزل السمحاق عن العظم بشكل كامل يؤدي إلى تشكل نسيج عظمي جديد ذي كثافة منخفضة في الفراغ المتشكل بين الطبقة الداخلية للسمحاق والعظم.